An Institutional Repository Publishing Model for Imperial College London Grey Literature. Issue 3 (16th November 2020) - Price, Robyn; Murtagh, John
ABSTRACT: In 2019 we became increasingly aware of authors at Imperial College London choosing to publish grey literature through local website PDF or full text hosting. Recognising the need to improve the institutional open access repository as a venue of choice to publish or co-publish grey literature, we developed a publishing model of identifiers (DOIs and ORCIDs) and metrics (indexing, citations and Altmetric coverage). Some of the incentives already existed in the repository but had not previously been explicitly communicated as benefits; whilst others required technical infrastructure development and scholarly communications education for authors. As of September 2020, a 206% increase in deposit of one type of grey literature has been observed on the previous full year, including Imperial's influential COVID-19 reports.